Modelling of rock mass fracturing, fragmentation and preconditioning to assist in caving design - Xu, Y-H; Li, Y; Jakubec, J; Thomas, A (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
The transition to deep, competent orebodies in block caving operations presents significant challenges regarding caveability, primary fragmentation, and seismic hazard management. However, quantifying the mechanistic interaction between stress-induced fractures and the natural discontinuities remains complex. This paper presents the application of the hybrid finite-discrete element method (FDEM) to simulate these coupled processes. Unlike conventional continuum or purely discrete approaches, FDEM explicitly models the transition from continuous to discontinuous media, allowing for the rigorous simulation of fracture propagation through intact rock. This study utilises 3D FDEM to integrate discrete fracture network (DFN) representations of in situ rock fabric with fracture propagation logic. Simulation results demonstrate that FDEM effectively captures the reduction in rock block volume resulting from progressive fracture initiation and coalescence under increasing loading levels, representing either caving-induced stress or hydraulic pressure in cave mining operations.
Keywords: block caving design